Selecting Core Outcomes for Randomised Effectiveness trials In Type 2 diabetes (SCORE-IT): a patient and healthcare professional consensus on a core outcome set for type 2 diabetes - James Harris; Paula R Williamson; John P H Wilding; Nicola L Harman; Jennifer Logue; Leigh Perreault; Dave Curry; R John Pemberton; Gareth Thompson; Sean Tunis; Serena Battaglia; Florence Bietrix; et al. (BMJ Open Diabetes Research & Care)
Objectives Heterogeneity in outcomes measured across trials of glucose-lowering interventions for people with type 2 diabetes impacts on the ability to compare findings and may mean that the results have little importance to healthcare professionals and the patients that they care for. The SCORE-IT study (Selecting Core Outcomes for Randomised Effectiveness trials In Type 2 diabetes) has addressed this issue by establishing consensus on the most important outcomes for non-surgical interventions for hyperglycemia in type 2 diabetes.Research design and methods A comprehensive list of outcomes was developed from registered clinical trials, online patient resources, qualitative literature and long-term studies in the field. This list was then scored in a two-round online Delphi survey completed by healthcare professionals, people with type 2 diabetes, researchers in the field and healthcare policymakers. The results of this online Delphi were discussed and ratified at a face-to-face consensus meeting.Results 173 people completed both rounds of the online survey (116 people with type 2 diabetes, 37 healthcare professionals, 14 researchers and 6 policymakers), 20 of these attended the consensus meeting (13 people with type 2 diabetes and 7 healthcare professionals). Consensus was reached on 18 core outcomes across five domains, which include outcomes related to diabetes care, quality of life and long-term diabetes-related complications.Conclusions Implementation of the core outcome set in future trials will ensure that outcomes of importance to all stakeholders are measured and reported, enhancing the relevance of trial findings and facilitating the comparison of results across trials.